Hyponatremia Evaluation and Treatment - Simon, Eric E. (Springer New York : Imprint: Springer, 2013)
Hyponatremia is a common electrolyte disorder found in a variety of settings. Manifestations range from subtle abnormalities to convulsions and death.  New treatment options, such as Antidiuretic Hormone (ADH) antagonists, have created the need for a resource presenting the latest evidence and clinical approaches.   Hyponatremia:  Evaluation and Treatment is a comprehensive review of hyponatremia, with an emphasis on managing this disorder from diagnosis to treatment.  The incidence and occurrence of acute and chronic hyponatremia in general terms are covered, as well as hyponatremia induced by drugs and exercise and disorders of the central nervous, cardiovascular and digestive systems.  Common clinical scenarios are presented along with both traditional and new methods of treatment.   Authored by experts on this disorder from around the world, experienced members of the medical community and trainees alike will find Hyponatremia as an indispensible guide to diagnosis, managing and treating patients with hyponatremia.  .